1998
DOI: 10.1159/000022375
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of the Coagulant and Fibrinolytic Profile of Human Pancreatic Carcinoma Cells

Abstract: The activation of coagulation and fibrinolytic pathways is well recognized in patients with malignant disease including those with carcinoma of the pancreas. The elaboration of activators and inhibitors of coagulation and of fibrinolysis has been assessed in 8 human pancreatic adenocarcinoma cell lines in vitro. Tissue factor (TF) was commonly synthesized with wide variations in the amount produced between cell lines, whereas its inhibitor (tissue factor pathway inhibitor, TFPI) showed lower but more consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].…”
supporting
confidence: 92%
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].It is interesting that the large majority of patients who develop VTE during chemotherapy have normal MP-TF activity, suggesting that an acute thrombotic event itself is not the cause of an elevated MP-TF activity. Our data point to a contribution of cancer cells themselves as (in) direct cause of elevated MP-TF activity and ask for novel studies better designed to study prospectively the relationship between chemotherapy, elevated MP-TF activity and venous thrombosis.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The mechanisms by which TFPI is increased in patients with cancer is not fully understood; however, increased synthesis by tumour cells or host cells is likely. Tumour‐associated macrophages 39 and various cancer cells have been shown to express TFPI 18, 142, 143, whereas small lung cell carcinoma, renal cell carcinoma and malignant melanoma did not 39. The absence of appropriately configured TF–FVII : Xa complex, required for TFPI‐binding, may be the cause.…”
Section: The Clinical Value Of Tfpimentioning
confidence: 99%
“…Офици-ально датой ее признания считается 1865 г., когда французский врач А. Труссо опубликовал лекцию, в которой описал несколько случаев пальпируемых опухолей брюшной полости, сопровожда-ющихся наличием поверхностных тромбофлебитов, высказав ги-потезу о возможной гиперкоагуляции, связанной с опухолью [5]. Впоследствии эта гипотеза нашла подтверждение, но при этом было показано и противоположное влияние компонентов систе-мы свертывания на прогрессию опухоли [6,7]. На сегодняшний день многие механизмы этой двусторонней взаимосвязи уже из-учены.…”
unclassified